Exploring entomopathogenic fungi from South Sumatra (Indonesia) soil and their pathogenicity against a new invasive maize pest, Spodoptera frugiperda - Siti Herlinda; OCTARIATI Noni; Suwandi Suwandi; Hasbi Hasbi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Herlinda S, Octariati N, Suwandi S, Hasbi. 2020. Exploring entomopathogenic fungi from South Sumatra (Indonesia) soil and their pathogenicity against a new invasive maize pest, Spodoptera frugiperda. Biodiversitas 21: 2955-2965. Fall armyworm (Spodoptera frugiperda) is a new invasive maize pest in Indonesia that can cause maize yield losses of 18 million tons/year. To overcome the pest, local-specific entomopathogenic fungi are needed. This study aimed to explore entomopathogenic fungi from soil in South Sumatra and to determine their pathogenicity against S. frugiperda larvae. The fungi exploration was carried out in the lowlands and highlands of South Sumatra and the pathogenicity of obtained isolates were tested against the third instar larvae. The entomopathogenic fungi found were Metarhizium spp. and were successfully isolated as many as 14 isolates. All of the isolates were pathogenic to S. frugiperda larvae (70.67?78.67% mortality), the most pathogenic caused 78.67% mortality and significantly suppressed the emergence of adults up to 81.2%. Unhealthy larvae had a dry, shrunken, shrinking, odorless body, and its integument was covered in mycelia and conidia like yellowish-white powdery mixed with dark green. The unhealthy pupae and adults were in the abnormal and malformation shape. The abnormal pupae were shorter in size, bent, the to-be wings got wrinkled, and darker color, while the unhealthy adults had folded wings and were unable to fly. The two most pathogenic isolates were found from the lowland (PirOI) and highland (CasPsPGA) soil of South Sumatra. In conclusion, both of these isolates had the potential to be developed into local-specific mycoinsecticides to control pest insects in the highlands and/or lowlands in Indonesia.